(3CSGSjGJ JObjb fXe GdeYdheGJ aj GdeDSSIs - (3ghGQjI(B, (3eHShWs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2023)
(3fXe hJcfhdhLjG GdeYdheGJ, JObjb fXe GdeYdheGJ hYdGbJg HGdJObjb GdGdcJQhfjefgG JObjb fXe GdeYdheGJ, hGdeMGSHI GdGdcJQhfjI, cPdc GdaQb hGdYdGbI eGHjf GdJObjb GdGdcJQhfjhJObjb fXe GdeYdheGJ(B.(3hCNjQG GdJObjb aj Xd GdJLGQI GdGdcJQhfjI(B.s
(3eQGLY U(B.161s
Keywords: (3GdJObjbs; (3eQGLYI GdMSGHGJs; (3fXe GdeYdheGJs